Interactions in distance education: A report from the other side. - Byron R. Burnham; Beth Walden (Adult Education Research Conference, 1997)
This observational study investigated the kinds of interactions among and between students, instructors, the media, and the environment in distance education courses. In addition to confirming the interaction types reported in the literature, learner-environment interaction was documented. Interaction chains, interaction objects, and interaction subjects were described.